Exploring how well MidCentral DHB cancer services are meeting the supportive needs of their patients : a mixed methods approach : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Manawatū, Aotearoa/New Zealand - Vitale, Renee (Massey University, 2021)
Cancer will affect most people in their lifetime, directly or through a family/whānau member or friend. It can have a profound impact on those affected, not just physically, but emotionally, socially, and spiritually. As those affected try to deal with cancer and its treatment, they experience certain needs to help cope with the experience. Supportive care aims to provide the support required to meet these needs. The current study aimed to find out how well MidCentral DHB cancer services are meeting the supportive care needs of their patients, using audit methodology. A mixed-method approach was employed to explore the perspectives of staff and patients. Surveys were utilised with both groups, and interviews were conducted with seven patients to further explore the supportive care needs and unmet needs of this group. The staff survey results found high agreement for having sufficient understanding of patient needs, however, staff were less confident in using tools to identify these needs with patients. Thematic analysis of the staff comments identified one key theme; constraints, and three subthemes: Limits of space and place; Important, but not practical; and Working within constraints. Overall, patient survey results found that most believed their needs were well met. Lower agreement was found with patients’ psychological, social and spiritual needs being identified and addressed. Thematic analysis of patient qualitative data identified four themes: 1. People will never forget how you made them feel (subthemes: positive interactions, just another case, and concern for staff); 2. Role of family/whānau (subthemes: Foundation of support and Nuances of support); 3. Lack of privacy and 4. The importance of communication and information needs across the continuum. Patients valued the positive interactions they had with staff and the role their family/whānau had in their experience. The other themes highlighted some unmet needs around privacy and communication.
Keywords: 520304 Health psychology